DNA methylation and transcription in HERV (K, W, E) and LINE sequences remain unchanged upon foreign DNA insertions - Weber, Stefanie; Jung, Susan; Dörfler, Walter (Epigenomics, 2016)
DNA methylation and transcriptional profiles were determined in the regulatory sequences of the human endogenous retroviral (HERV-K, -W, -E) and LINE-1.2 elements and were compared between non-transgenomic and plasmid-transgenomic cells.DNA methylation profiles in the HERV (K, W, E) and LINE sequences were determined by bisulfite genomic sequencing. The transcription of these genome segments was assessed by quantitative real-time PCR.In HERV-K, HERV-W and LINE-1.2 the levels of DNA methylation ranged between 75 and 98%, while in HERV-E they were around 60%. Nevertheless, the HERV and LINE-1.2 sequences were actively transcribed. No differences were found in comparisons of HERV and LINE-1.2 CpG methylation and transcription patterns between non-transgenomic and plasmid-transgenomic HCT116 cells.The insertion of a 5.6 kbp plasmid into the HCT116 genome had no effect on the HERV and LINE-1.2 methylation and transcription profiles, although other parts of the HCT116 genome had shown marked changes. These repetitive sequences are transcribed, probably because the large number of HERV and LINE-1.2 elements harbor copies with non- or hypo-methylated long terminal repeat sequences.
EVALuna2:8330